Text normalization of code mix and sentiment analysis - Sharma, Shashank; Srinivas, Pykl; Balabantaray, Rakesh Chandra (2015 International Conference on Advances in Computing, Communications and Informatics (ICACCI), 2015)
The field of getting insights from various text forms such as feedback, opinions, blogs and classifying them based on their polarity as positive or negative is known as sentiment analysis. But from last few years we find huge amount of code - mix (mixture of two languages) text available on social media. This text is available in Romanized English format in Indian social media, which is the transliteration of one language into another, which demands normalization to get further insights into the text. In this paper, we have presented various methods to normalize the text and judged the polarity of the statement as positive or negative using various sentiment resources.